Influence of Socio-Cultural Factors on Gender Participation in Basic Adult Literacy Development Programme in Nakuru West Sub-County, Nakuru County, Kenya - Kuria, Virginiah (American Journal of Education and Learning, 2021)
The aim of this study was to examine the influence of socio-cultural factors on gender participation in basic adult literacy development programme. The study was guided by the institutional theory and employed the descriptive research design. It targeted a population of 1,564 individuals consisting of 17 adult education instructors, as well as, 1,547 learners that were involved in basic adult literacy development programmes in Nakuru West Sub-County. From the population, a sample was 16 instructors and 140 adult learners was selected using the clustered random sampling technique. Semi-structured questionnaires were used to collect data from the learners while interview guides were used to gather data from instructors. Quantitative data was analysed using percentages and the chi-square test while qualitative data was analysed using the thematic technique. Results showed that women had greater participation in basic adult literacy development programme in Nakuru West than men in terms of enrolment, class attendance, class involvement, and course completion. The low participation of men in basic adult literacy development programme was influenced significantly by the gender of the instructors (p =0.046). Based on these findings, the study recommends that the directorate of adult education in Nakuru West and instructors should incorporate intercultural education in the basic adult literacy development programme and promote gender parity in the programme’s teaching workforce.